Hubungan Antara Tingkat Pengetahuan Dan Perilaku Anak Sekolah Dasar Mengenai Pemilihan Makanan Jajanan Dengan Status Gizi Di SD Negeri Kudu 02 Baki Kabupaten Sukoharjo - ROSYIDAH, Cholifatur; , Muwakhidah, SKM, M.Kes; , Eni Purwani, S.Si., M.Si (2015)
INTRODUCTION: Child is an age group with risk of disease transmission through food and beverage. Children buy snacks and foods according to their want without considering what ingredients are contained the snacks and foods. Snacks and foods that are not meeting health and nutritional requirements adequately will threat health and appetite of the children. If it occurs for long time, it will affect nutritional status. PURPOSE: Correlation Between level of Knowledge and Behavior of Elementary School Student about Food and Snack preference and Nutritional Status of the Children in SD Negeri Kudu 02 Baki, Sukoharjo Regency. METHOD: The research is observational one with cross-sectional approach. Population of the research is all students of class IV-VI amounting to 60 children. Sample of the research is 41 children. Correlation is examined by using Rank Spearman test. RESULTS: Results of the research indicated that the elementary school students had good knowledge level of food and snacks preference, namely 70.7%. Most of the elementary school students had not good behavior about food and snack preference, namely 58.5%. Majority of the students had normal nutritional status, namely 78%, whereas children with abnormal nutritional status were 22%. Result of The Rank Spearman test showed that correlation between knowledge level and preference of food and snack was p-value = 0.7771 and correlation between behavior and preference of food and snack was p-value = 0.540. CONCLUSION: There is no correlation between level of knowledge and behavior of elementary school students about food and snack preference and nutritional status.